Da negação ao reconhecimento: a educação escolar indígena e a educação intercultural: implicações, desafios e perspectivas - Oliveira, Jasom de (2012)
The dissertation investigates the indigenous education at schools in Brazil, from the historical movements, their construction processes, contexts, meanings and theoretical assumptions, seeking to identify, currently, their educational proposal of an intercultural character, possible challenges and perspectives. The study makes use of bibliographic research. This will be historical, concerning educational strategies imposed on indigenous peoples since the arrival of Portuguese colonists until the Federal Constitution of 1988, documentary, with the official educational documents which propose and regulate indigenous education, from the promulgation of the 1988 Constitution; and theoretical, with the findings of the offer of an intercultural education for indigenous peoples and the implications, challenges and perspectives that this new proposal brings to indigenous education and beyond it. The first chapter contextualizes and characterizes the history of domination of indigenous peoples in Brazil since the beginning of the Portuguese colonization until the advent of the Federal Constitution of Brazil in 1988. The religious movements and legislative processes were strongly present in the history of domination; therefore, their performances are highlighted in this research. The second chapter identifies the changes in the Constitution of 1988, considered a historical milestone in the recognition of the indigenous peoples, about indigenous education and educational legislative changes resulting from its promulgation. This research highlights along each transformation that is approached the new educational provision prescribed by educational documents, legislated from the Education Law (Lei das Diretrizes e Bases da Educação Nacional - LDB) of 1996: intercultural education for indigenous peoples. The third chapter identifies, analyzes and discusses the proposal of intercultural education for indigenous peoples that composes the Brazilian indigenous education currently. From the systematization of what the cross-cultural perspective is, especially in the educational field, it is discussed the consequences of offering an intercultural education present in the indigenous education at school, with its implications, challenges and perspectives.